Модульно-рейтингова система в дистанційному навчанні - Кухаренко, Володимир Миколайович; Рибалко, Олена Володимирівна; Твердохлєбова, Наталя Євгеніївна (Украинская ассоциации дистанционного образования, 2005)
The article contains information about the tutor’s influence on process of mastering of the knowledge by students in distant training. The levels of tutor’s productive activity are allocated. Besides we have discussed the peculiarities of tutor’s activity while teaching in the distant course.
Keywords: навчання в співробітництві; різнорівневе навчання; модульне навчання; професійні уміння